2010
DOI: 10.1016/j.jasms.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Native electrospray and electron-capture dissociation in FTICR mass spectrometry provide top-down sequencing of a protein component in an intact protein assembly

Abstract: The intact yeast alcohol dehydrogenase (ADH) tetramer of 147 kDa was introduced into a FTICR mass spectrometer by native electrospray. Electron capture dissociation of the entire 23ϩ to 27ϩ charge state distribution produced the expected charge-reduced ions and, more unexpectedly, 39 c-type peptide fragments that identified N-terminus acetylation and the first 55 amino acids. The results are in accord with the crystal structure of yeast ADH, which shows that the C-terminus is buried at the assembly interface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
138
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 18 publications
6
138
0
Order By: Relevance
“…However, expectedly, sequence coverage was considerably more comprehensive using CAD and IRMPD in [332] than our approach, involving HCD AIF. In our study, similar to the previous reports [296,332], the sequence origin of the detected fragment ions can be correlated to the outer surface regions of the complex and protein termini.…”
Section: Native Cze-ms Of Mixtures Of Complex-forming Proteinssupporting
confidence: 91%
See 3 more Smart Citations
“…However, expectedly, sequence coverage was considerably more comprehensive using CAD and IRMPD in [332] than our approach, involving HCD AIF. In our study, similar to the previous reports [296,332], the sequence origin of the detected fragment ions can be correlated to the outer surface regions of the complex and protein termini.…”
Section: Native Cze-ms Of Mixtures Of Complex-forming Proteinssupporting
confidence: 91%
“…The authors correlated this fragmentation pattern with the X-ray crystal structure of the ADH tetramer that showed that the N terminus of the protein is exposed and available for fragmentation, while the C terminus is hidden and involved in the interface of the subunits. Fragmentation coverage was also limited as a result of the formation of charge-reduced ADH1 tetramer species by ECD, resulting in no dissociation of ADH1 subunits from the tetrameric complex [296]. In our study, in addition to N-terminal fragments we also observed C-terminal fragment ions (Figure 4-6A).…”
Section: Native Cze-ms Of Mixtures Of Complex-forming Proteinsmentioning
confidence: 51%
See 2 more Smart Citations
“…In these experiments, charge reduction and the subsequent transmission and detection of the resulting extremely high m/z species typically require instrument modifications [15,18]. Limited charge reduction is also typically observed as a side reaction in electron capture (ECD) and electron transfer dissociation (ETD) experiments, without instrument modification, particularly when working with intact proteins [19][20][21][22][23][24]. In addition, ECD or ETD fragments can remain bound to each other by noncovalent interactions so that they appear as chargereduced precursor ions in the spectra [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%